Environmental impacts of offshore wind installation, operation and maintenance, and decommissioning activities: A case study of Brazil. (July 2021) - C, O. Mauricio Hernandez; Shadman, Milad; Amiri, Mojtaba Maali; Silva, Corbiniano; Estefen, Segen F.; La Rovere, Emilio
Abstract: The objective of the paper is to perform a review of the environmental impacts of the installation, operation and maintenance (O&M), and decommissioning of offshore wind technologies. At first, a comprehensive review is presented on offshore wind technologies and techniques related to the installation, O&M, and decommissioning stages. Then a thorough review of environmental issues using the main available studies in the literature associated with the activities of each stage is performed. The review employs an activity–stressor–receptor–impact framework in which the possible positive or negative impacts of an environmental stressor on a specific receptor are identified for each activity, such as pile driving, cabling, blade rotation, etc. Additionally, a case study of Brazil addresses regions with biological resources, marine protected areas, and offshore wind hotspots considering atmospheric reanalysis along the coastline. Moreover, the presence of the offshore oil and gas (O&G) industry is discussed as an important influence on the development of offshore wind projects in Brazil. Graphical abstract: Highlights: Environmental impacts analyzing the activity–stressor–receptor–impact relationship. Extremely high biological importance areas within Brazilian hotspots shallow water. O&G activities along Brazilian hotspots of the Northeast and the Southeast coastline. Recommendations for the offshore wind environmental licensing process in Brazil.